2016
DOI: 10.1038/srep29594
|View full text |Cite
|
Sign up to set email alerts
|

A Hidden Portrait by Edgar Degas

Abstract: The preservation and understanding of cultural heritage depends increasingly on in-depth chemical studies. Rapid technological advances are forging connections between scientists and arts communities, enabling revolutionary new techniques for non-invasive technical study of culturally significant, highly prized artworks. We have applied a non-invasive, rapid, high definition X-ray fluorescence (XRF) elemental mapping technique to a French Impressionist painting using a synchrotron radiation source, and show ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…The detector was developed jointly at Brookhaven National Laboratory (Upton, NY) and CSIRO (Clayton, VIC, Australia) and is described in detail elsewhere [24,25]. Previous models of this detector have been successfully applied to elemental mapping of other works of art [26,27].…”
Section: Synchrotron Radiation X-ray Fluorescence Mapping (Sr-xrf)mentioning
confidence: 99%
“…The detector was developed jointly at Brookhaven National Laboratory (Upton, NY) and CSIRO (Clayton, VIC, Australia) and is described in detail elsewhere [24,25]. Previous models of this detector have been successfully applied to elemental mapping of other works of art [26,27].…”
Section: Synchrotron Radiation X-ray Fluorescence Mapping (Sr-xrf)mentioning
confidence: 99%
“…For example, Romano et al reported a lateral resolution of up to 25 μm, scanning at a speed of 100 mm s −1 with 500 μm pixel size . Thurrowgood et al presented 31.6 megapixel high‐definition XRF mapping using synchrotron source . Moreover, studies concerning improvements to large data files acquisition and processing have been gaining importance, as has the coupling of MA‐XRF with other techniques, for example, hyperspectral imaging, X‐ray absorption spectroscopy, or optical coherence tomography …”
Section: Introductionmentioning
confidence: 99%
“…Until recent times, micro‐ and macro‐XRF mapping/imaging analysis was possible only by synchrotron radiation requiring the transport of precious artworks to large scale facilities . Only in the very last years the advancement in instrumental technologies has made it possible to transpose the technique to laboratory and to in‐s itu applications .…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Until recent times, micro-and macro-XRF mapping/imaging analysis was possible only by synchrotron radiation requiring the transport of precious artworks to large scale facilities. [9][10][11] Only in the very last years the advancement in instrumental technologies has made it possible to transpose the technique to laboratory and to in-situ applications. [2,3,12,13] However, finding a good compromise which takes into account instrument portability, large scans, beam dimension, count rates, and acquisition time is still very challenging.…”
Section: Introductionmentioning
confidence: 99%